Ultrafast mid-infrared laser spectroscopy : applications and technique developments - Yan, Suxia (2012)
This thesis discusses applications and technique development in ultrafast mid infrared nonlinear spectroscopies. After a brief introduction in Chapter 1, the vibrational dynamics of a metal carbonyl compound Os3(CO)12 are investigated with mid-infrared (MIR) pump-probe spectroscopy in Chapter 2. Specifically the vibrational relaxation dynamics of the four infrared active carbonyl stretching normal modes of Os3(CO)12 were measured using broad-band frequency resolved MIR pump-probe spectroscopy. The frequency resolved pump-probe traces measured at the fundamental absorptions exhibit marked differences: The two axial modes at frequencies of 2068 cm-1 and 2034 cm-1 yield similar bi-exponential decay traces, while the two equatorial modes at 2014 cm-1 and 2002 cm-1 show an extra rising component. The axial-equatorial combination anharmonicity constants are found to be near zero. This results in the appearance of the pump-probe signals of these combination bands at the same frequencies as the fundamental transitions, leading to interference and the resultant anomalous rising features. If unaccounted for, these interferences may lead to erroneous conclusions about the dynamics of these vibrational stretches. To avoid such pitfalls, it is therefore imperative to resolve such ambiguities. No obvious direct vibrational energy transfer between the axial and equatorial CO stretching modes was observed.